Psidium cattleianum como posible tratamiento del estrés oxidativo causado por infección de SARS-COV-2: Psidium cattleianum as a possible treatment for oxidative stress caused by SARS-CoV-2 infection - Carbajal-Lázaro, Diana Carolina (2022)
The SARS-CoV-2 virus presents a lot of proteins in its structure that facilitate host cell infection,generating an increase in the concentration of angiotensin II and activating multiple signalingpathways that stimulate the NADPH oxidase enzyme complex and enzymes that take part in theinflammatory answer. As a consequence, there is an increase in reactive oxygen species (ROS)that damage different proteins, lipids and nucleic acids. Given this, Psidium cattleianum cancapture free radicals or inhibit the formation of ROS by transferring hydrogen atoms andelectrons. For that, this research has the main objective to determine the influence of Psidiumcattleianum as a possible treatment of oxidative stress caused by the SARS-COV-2 infection inorder to consider the consumption of this berry as a possible alternative as an antioxidanttreatment.Objective: To determine the influence of Psidium cattleianum as a possible treatment ofoxidative stress caused by SARS-Cov-2 infection.Materials and methods: The information collected was obtained by consulting the bibliographicsources: Pubmed / MEDLINE, Google Scholar, Cochrane, SciELO, ScienceDirect and Latindex.Conclusion: The consumption of Psidium cattleianum is proposed as a complementary treatmentto reduce oxidative stress in patients infected by SARS-CoV-2.